COMPARISON OF PEPPERMINT AROMATHERAPY AND STANDARD THERAPY ON THE QUALITY OF LIFE OF PREGNANT WOMEN WITH EMESIS GRAVIDARUM - Rahmi Nurrasyidah; Lutfiana Puspita Sari (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2025)
Nausea and vomiting during the first trimester of pregnancy can occur at any time and cause a decrease in quality of life. This study aims to compare standard therapy and peppermint aromatherapy on the quality of life of pregnant women in the first trimester. The study design is quasi-experimental using a control group. Pre- and post-tests were calculated in both groups. Standard therapy was given to the control group and peppermint aromatherapy was given to the intervention group with a sample size of 30 people per group. Subjects were selected using simple random sampling with the inclusion criteria of pregnant women aged 6-20 weeks with mild to moderate nausea and vomiting, a normal sense of smell, no digestive diseases, no mental health problems, no history of serious illnesses, no obstetric complications, no alcohol consumption, and no smoking. Data analysis used the Mann-Whitney test and the McNemar test. The results showed a significant difference in the quality of life scores of pregnant women between the control and intervention groups. The quality scores of pregnant women differed significantly on the 4th day of peppermint aromatherapy administration. In conclusion, this study shows that the quality of life in the standard therapy group is higher than in the intervention group. Increasing the intervention time is recommended for more valid results.